The Flash Card Sebagai Media Petunjuk Penggunaan Insulin di Puskesmas Paal Merah I Kota Jambi: FLASH CARD SEBAGAI MEDIA PETUNJUK PENGGUNAAN INSULIN DI PUSKESMAS PAAL MERAH I KOTA JAMBI - Rahmadina, Rahmadina; Andriani, Medi; Sutrisno, Deni (Jurnal SOLMA, 2023)
Background: Diabetes Mellitus is a type of disease that occurs due to abnormalities in insulin secretion. Many cases occur patients are not compliant in using drugs due to lack of patient knowledge and understanding. This study aims to see if there is an influence of knowledge already and before the provision of Flash card media as education for diabetes mellitus patients at the Paal Merah I Health Center in Jambi City. Methods: Pre-experimental pretest-posttest research. The sample of this study consisted of 57 samples. Data collection in this study was using pretest-posttest and secondary data. The analysis used Wilcoxon's statistical test with p Value = 0.000. Results: There was an increase in knowledge in diabetes mellitus patients who used insulin with p value = 0.000. Determinants associated with the incidence of diabetes mellitus are gender, age and occupation. Conclusion: Increased knowledge in diabetes mellitus patients using insulin